Correction method for mechanical performance testing instrument with tension–torsion coupling loading. (31st August 2018) - Liu, Changyi; Ma, Zhichao; Zhou, Liming; Qiao, Yuansen; Liu, Zeyang; Liu, Xianhua; Zhang, Shizhong; Zhao, Hongwei
Abstract: In our previous study, an instrument for characterizing mechanical properties under multi-mechanical load and multi-physical field coupling conditions was designed and constructed. Given the structural interference, the linear and shear strains in tension–torsion coupling testing were measured indirectly using linear and circular grating encoders rather than the extensometers in a conventional material testing machine. Accordingly, to correct the experimental curves measured using grating encoders, a correction method was proposed using equations based on the analysis of specimen geometry and instrument structure by elasticity theory. The feasibility of the correction method under single load and tension–torsion coupling loads were verified by the contrast tests among curves of grating encoders', curves of extensometers, and results of a digital image correlation (DIC) measuring system. Test results illustrate that the correction method can convert the displacement measured using grating encoders to the deformation of the specimen in the elastic range, and the measuring error of elastic moduli can be reduced to approximately 1/5–1/50 of the original measurement results. The defect on accuracy of this instrument, which is incompatible with extensometers, can be compensated. Overall, the main sources of error in these devices are the deformation of the load cell and that on the non-gage section of specimen. This conclusion can provide guidance on the design of other similar devices.